Impact of acute mental fatigue on cricket-related performance measures in university level indoor cricket players - Michelle Evans; Travis Blood; Rachel L. Bevins (Frontiers in Sports and Active Living)
Acute mental fatigue affects elements of sporting performance such as technical performance or decision making in high-level athletes, however less is known about the effects in non-elite sport. The aim of this study was to examine the effect of acute mental fatigue on cricket specific performance and reaction time in university-level cricketers during the indoor competitive season. Ten male university cricket players (Age 18–23 years, height 183.3 ± 8.7 cm, body mass 88.5 ± 19.8 kg) performed baseline testing, and two experimental test conditions separated by a 48-hour washout. Mental fatigue was induced using two different tasks: a 30-min smartphone-based Stroop test (Stroop) and a 30-min smartphone-streaming based cricket video (Film). Performance outcomes were assessed through the English Cricket Board's Run2 test for sprint performance and the Batak test for reaction time. The results indicated that both the Stroop and Film conditions induced mental fatigue compared to Baseline [χ2 (2) = 19.16, p < 0.001], although the Film condition produced only a small increase in fatigue. Cricket Run2 times were negatively affected by both the Stroop and Film tasks [F(2) = 24.83, p < 0.001]. Acute mental fatigue, induced by either an app-based Stroop test or an app-based video stream, negatively affected cricket-relevant performance in university level indoor cricketers.